Pengaruh Jalan Alternatif Terhadap Volume Lalu Lintas dan Tingkat Pelayanan Jalan Bukit Kaminting Kota Palangka Raya - Bella, Sinta; Desriantomy, Desriantomy; Elvina, Ina (Jurnal Basement : Jurnal Teknik Sipil, 2025)
Bukit Kaminting is a road known for its heavy traffic because it is located in a residential area, shops, and the education area of Palangka Raya University. Not only motorcycles and cars, but trucks with loads also often pass on the road. This road condition also often occurs congestion and even traffic accidents. The purpose of this study is to determine the amount of traffic, analyze the quality and capacity of road services in Bukit Kaminting from the intersection segment of Jl. Tingang to the intersection of Jl. Bukit Pararawen. Quantitative approach and PKJI 2023 data analysis are the research methods used. The results of this study show that the volume of peak traffic on Jl. Bukit Kaminting (intersection of Jl. Tingang to intersection of Jl. Bukit Pararawen) with alternative roads, occurred on Saturday, February 15, 2025, from 16.30 to 17.30 WIB, with an amount of 1638 smp / hour. The capacity of the road section on Jl. Bukit Kaminting from the intersection segment of Jl. Tingang to the intersection of Jl. Bukit Pararawen is 2214.324 smp / hour. The degree of saturation (DJ) value on Jl. Bukit Kaminting (intersection Jl. Tingang to intersection Jl. Bukit Pararawen) with alternative roads, which is 0.74 with LoS category D. The existence of alternative roads can reduce the degree of saturation by 20% from 0.92 to 0.74.